2006
DOI: 10.1007/bf02969309
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization andin vitro evaluation of triptolide-lysozyme conjugate for renal targeting delivery of triptolide

Abstract: A triptolide-lysozyme (TP-LZM) conjugate was synthesized to achieve renal specific delivery and to reduce the side effects of triptolide. Triptolide was coupled to lysozyme through succinic via an ester bond with an average coupling degree of 1 mol triptolide per 1 mol lysozyme. The lysozyme can specifically accumulate in the proximal tubular cells of the kidney, making it a potential carrier for targeting drugs to the kidney. The structure of triptolide succinate (TPS) was confirmed by IR, 1H-NMR, MS and UV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Endogenous low molecular weight proteins (LMWP), lysozyme, was utilized as renal-specific drug carriers to form 14-succinate triptolide-lysozyme (TPS-LZM) conjugate [14][15][16]. Our data demonstrated the efficacy and safety of this PTEC specific TP therapeutics as well as its potential clinical applications as a local immunosuppressant.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Endogenous low molecular weight proteins (LMWP), lysozyme, was utilized as renal-specific drug carriers to form 14-succinate triptolide-lysozyme (TPS-LZM) conjugate [14][15][16]. Our data demonstrated the efficacy and safety of this PTEC specific TP therapeutics as well as its potential clinical applications as a local immunosuppressant.…”
Section: Introductionmentioning
confidence: 68%
“…14-Succinate TP was synthesized and coupled to LZM and labeling of TPS-LZM with FITC was carried out as described previously, FITC was conjugated to LZM [14,17]. Briefly, 1 mg of TPS-LZM was dissolved in carbonate buffer solution (PBS, pH 7.2).…”
Section: Preparation Of Tps-lzm Conjugate and Fitc-labeled Tps-lzmmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of TP under the following conditions has been studied: (1) the stability of TPS-LZM in the sample preparation process; and (2) the stability of TP after extraction from the kidney homogenate samples. Our preliminary study showed that it is the lysosomal enzymes that are responsible for the hydrolysis of TPS-LZM in the kidney (Zheng et al, 2007). To avoid enzymatic hydrolysis and subsequent release of free TP during the sample storage and preparation, we adopted rapid liquid-nitrogen freezing and organic solvent extraction.…”
Section: Stabilitymentioning
confidence: 99%
“…To address these issues with the potential eventual clinical applications, we designed and prepared the renaltargeting 14-succinyl triptolide-lysozyme (TPS-LZM, Fig. 1, III) (Fransen et al, 1991;Haas et al, 1993Haas et al, , 1997Zheng et al, 2007). Although many studies have been carried out on the immunosuppressant effects of TP and its derivatives in renal diseases, most of them have focused on pharmacological features.…”
Section: Introductionmentioning
confidence: 99%